2022
DOI: 10.1093/infdis/jiab598
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Cluster Linked to Aerosol Transmission of SARS-CoV-2 via Floor Drains

Abstract: Background Recently, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission through exposure to aerosols has been suggested. Therefore, we investigated the possibility of aerosol SARS-CoV-2 transmission within an apartment complex where residents reported testing positive for SARS-CoV-2 despite having no direct contact with other SARS-CoV-2–infected people. Methods Information on symptom onset and exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 16 publications
3
27
0
1
Order By: Relevance
“…Fifty six additional reports identified from the Comber et al rapid review 21 and by citation analysis were also assessed. From these 146 reports, 124 were excluded (see supplementary material 1 (section 3) for list of reasons for exclusion), and 22 reports 1 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 relating to 18 studies were included. When two or more reports related to the same study, we considered the most comprehensive report as the main publication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty six additional reports identified from the Comber et al rapid review 21 and by citation analysis were also assessed. From these 146 reports, 124 were excluded (see supplementary material 1 (section 3) for list of reasons for exclusion), and 22 reports 1 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 relating to 18 studies were included. When two or more reports related to the same study, we considered the most comprehensive report as the main publication.…”
Section: Resultsmentioning
confidence: 99%
“… 36 Eight studies were conducted in Asia, 34 35 36 37 38 39 40 45 five in Europe, 41 43 44 47 48 three in Oceania, 32 33 46 and two in the United States. 1 42 Three studies reported on transmission between flats in apartment blocks, 38 39 40 two in quarantine hotels, 32 33 two in restaurants, 34 35 two in buses, 36 37 one in a food processing factory, 41 one in a courtroom, 43 one in an office, 44 one in a fitness facility, 42 one in a department store, 45 and four during singing events. 1 46 47 48 All the outbreaks occurred in 2020, except for one in January 2021 in South Korea 40 (before vaccine rollout started in this country) and one in July 2021 in a quarantine hotel in New Zealand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). Vertical transmission evidence for the SARS-CoV-2 has been previously reported [ 36 ]. The VAV system started at 6:00 and turned off at 22:00.…”
Section: Case Study – Us Doe Large Office Prototype Buildingmentioning
confidence: 99%
“…Empirical evidence has been reported for aerosol zonal transmission in an Eastern Canadian hospital [ 35 ]. Taewon et al [ 36 ] have also suggested the possibility of SARS-CoV-2 transmission between different floors of an apartment building. In their epidemiology investigation, five of nineteen reported cases claimed no direct contact with other residents in the building.…”
Section: Introductionmentioning
confidence: 99%